A Comprehensive Review on Weight Gain following Discontinuation of Glucagon-Like Peptide-1 Receptor Agonists for Obesity - Ibrahim Abdullah bin Ahmed (Hindawi Limited, 2024)
Obesity is considered the leading public health problem in the medical sector. The phenotype includes overweight conditions that lead to several other comorbidities that drastically decrease health. Glucagon-like receptor agonists (GLP-1RAs) initially designed for treating type 2 diabetes mellitus (T2DM) had demonstrated weight loss benefits in several clinical trials. In vivo studies showed that GLP-1RA encourages reduced food consumption and consequent weight reduction by stimulating brown fat and enhancing energy outlay through the action of the sympathetic nervous system (SNS) pathways. Additionally, GLP-1RAs were found to regulate food intake through stimulation of sensory neurons in the vagus, interaction with the hypothalamus and hindbrain, and through inflammation and intestinal microbiota. However, the main concern with the use of GLP-1RA treatment was weight gain after withdrawal or discontinuation. We could identify three different ways that could lead to weight gain. Potential factors might include temporary hormonal adjustment in response to weight reduction, the central nervous system's (CNS) incompetence in regulating weight augmentation owing to the lack of GLP-1RA, and β-cell malfunction due to sustained exposure to GLP-1RA. Here, we also review the data from clinical studies that reported withdrawal symptoms. Although the use of GLP-1RA could be beneficial in multiple ways, withdrawal after years has the symptoms reversed. Clinical studies should emphasize the downside of these views we highlighted, and mechanistic studies must be carried out for a better outcome with GLP-1RA from the laboratory to the bedside.